PEDOMAN HIDUP ISLAMI DALAM BIDANG SENI DAN BUDAYA - Raudah Nailati .; Ainun Tsaqifah; Abbas; Dahlan Lama Bawa (STKIP Subang, 2025)
This article aims to examine the role of Islamic guidelines for living in guiding the development of Islamic-informed arts and culture. Through a qualitative approach, analyzing texts from the Quran, Hadith, and related literature, this study outlines the basic Islamic principles that serve as the foundation for creating and evaluating works of art and cultural expression. The results indicate that Islamic guidelines for living emphasize truth, beauty, moral truth, and the unity of form and content in art, while avoiding elements that are offensive, demeaning, or contrary to religious values. The paper also discusses examples of the application of these principles in various forms of art and culture, such as architecture, music, performing arts, and literature, as well as their contribution to building a harmonious and characterful society. This study concludes that Islamic guidelines for living do not hinder artistic and cultural creativity but rather provide a profound framework for creating meaningful, useful works oriented toward human well-being and divinity.